Pelatihan Aplikasi Pembelajaran Berbasis IT sebagai Media Belajar pada Guru SMA Negeri 1 Dewantara - Afni Sinaga, Nurul; Mahmuzah, Rifaatul; Elisyah, Nur; Fatwa, Islami (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2024)
The important need for the development of technology in education requires teachers to be able to use technology proficiently so as to provide effective and innovative learning to students in the classroom. the implementation of observations and interviews conducted by the service team found that not all teachers of SMAN 1 Dewantara used information technology in the learning process. Some teachers have implemented IT-based learning in the classroom but are not maximized in their delivery in class. Based on these problems, the service team conducted IT-based learning application training for teachers of SMAN 1 Dewantara. The training aims to increase teachers' knowledge in the field of technology and can be a reference for teachers in applying active, creative and innovative and fun learning methods in the classroom. The training method is done by inquiry or direct practice. The result of this service activity is that teachers are able to use IT-based learning and can apply it in the teaching and learning process in class. The activities carried out received positive results from the school and hoped that activities like this could be carried out again at a later time.